Role for the terminal clasp of hiv-1 gp41 glycoprotein in the initiation of membrane fusion - Lay, C.; Ludlow, L.; Stapleton, D.; Bellamy-McIntyre, A.; Ramsland, Paul; Drummer, H.; Poumbourios, P. (2011)
The binding by HIV-1 gp120 to CD4 and a chemokine receptor activates the membrane fusion glycoprotein, gp41. The fusion function of gp41 involves the refolding of its core into a 6-helix bundle, which apposes the lipophilic termini (the fusion peptide and transmembrane domain) and the associated cell and viral membranes, leading to their fusion. In this study, we examined the functional role of the polar segment and membrane proximal external region (MPER), which link the fusion peptide and transmembrane domain, respectively, to the core domain and interact to form a terminal clasp adjacent to the core. Limited proteolysis indicated that the terminal clasp is destabilized by simultaneous I535A/V539G mutations within the polar segment and mutations within the MPER. The destabilizing effects of I535A/V539G correlated with defective cell-cell fusion, viral entry, and viral replication. By using lipophilic and cytoplasmic fluorescent dye transfer assays, we found that terminal clasp destabilization is linked to a block in the lipid mixing/hemifusion phase of the membrane fusion cascade. Because the biosynthesis of the prefusion gp120-gp41 complex did not appear to be affected by I535A/V539G, we infer that the hemifusion block is due to a specific effect on the trimer of hairpins conformation of gp41. By contrast, the decreased fusion function of the MPER mutants correlated with a decrease in the interfacial hydropathy of the MPER sequence, suggesting that the prefusion Env complex had been adversely affected in these cases. These findings reveal a novel conserved functional target for the discovery of fusion inhibitors. © 2011 by The American Society for Biochemistry and Molecular Biology, Inc.